The Exercise of Learner Autonomy in a Virtual EFL Course in Colombia - Paula Andrea Bedoya (Asociación Colombiana de Profesores de Ingles, 2014)
This case study explores how a group of graduate students manifest autonomy in an English as a Foreign Language virtual course at a Colombian university. Analysis of questionnaires, forums, and interviews showed that students manifested attitudes that led to autonomy such as motivation and commitment at the beginning of the course, but they also manifested high levels of dependence and lack of self-confidence. Later, they became more confident and performed more independently, two attitudes closely-related to autonomy. Furthermore, the results show that factors such as course design, the platform, and the teacher's role influenced the students' exercise of autonomy. Finally, the need for designing virtual English as a Foreign Language courses that promote autonomous learning and the teachers' and the students' roles in virtual environments are discussed.